2021
DOI: 10.1021/acsenergylett.1c02380
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Experiment: Cascading of Thermocatalysis and Electrolysis in Oxygen Evolution Reactions

Abstract: The role of elevated temperatures in electrolysis has generally been regarded as accelerations of electron transport, mass transport, and adsorption/desorption processes. In the present work, with first-principles calculations, we demonstrate that thermally activated on-surface reactions can significantly increase the efficiency of energy conversions in electrolysis via a thermally and electrically cascaded mechanism. In the oxygen evolution reaction (OER), to be specific, the formation of high-energy *OOH on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…The optimized atomic structures of *OH, *O, and *OOH intermediates on three Fe-MOF monolayers are diagnosed by considering different adsorbed sites and conformations ( Figures S2–S4 ). It is found that their reaction sites are the same as Fe atoms ( Figure 6 ), which is in agreement with those of other MOF materials [ 22 , 24 ].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The optimized atomic structures of *OH, *O, and *OOH intermediates on three Fe-MOF monolayers are diagnosed by considering different adsorbed sites and conformations ( Figures S2–S4 ). It is found that their reaction sites are the same as Fe atoms ( Figure 6 ), which is in agreement with those of other MOF materials [ 22 , 24 ].…”
Section: Resultssupporting
confidence: 88%
“…They are ( 1 S4). It is found that their reaction sites are the same as Fe atoms (Figure 6), which is in agreement with those of other MOF materials [22,24]. The OER free energy diagram at 0.00 V, 1.23 V, and work potential is depicted in Figure 6.…”
Section: Oersupporting
confidence: 83%
See 3 more Smart Citations